A Study of Empowerment of Mudarabah Practices in Facing Covid 19 Endemic Challenges in Malaysia. - Mohamed Shaarani, Ahmad Zakirullah; Djasriza bt Jasin; Mohd Noor Adzwan Bin Adam (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Mudarabah is a type of partnership contract in Islamic banking and finance. The salient conditions of the contract are that capital is contributed by the capital provider to the entrepreneur and profits are shared between the two while losses are fully borne by the former. Despite the many advantages of the mudarabah contract as a financing instrument, it is not as popular as other financing concept, especially debt-based financing. This phenomenon is due to some issues associated with this contract, making it less attractive to investors. Therefore, the focus of this study is to discuss the practices of mudarabah contract, particularly concerning the constraints in its implementation and the measures to strengthen it to make it remain relevant, especially in developing the capacity and capability of entrepreneurs affected by the Covid-19 pandemic. This study fully employed the library research method in which information was obtained from classical and modern literature pertaining to mudarabah. Current information and data were analysed to come up with suggestions and measures for strengthening the application of mudarabah. The study found that although mudarabah has been widely practised in the Islamic financial system, the practice is limited to receiving funds in the form of deposits rather than direct financing from banks and investors to entrepreneurs due to certain risks associated with the contract that makes it incompatible with the prevailing banking system. Several steps have been identified to empower mudarabah, such as expanding the mudarabah application through the investment account platform (IAP), adopting the interest scheme approach, upskilling and training entrepreneurs, introducing mudarabah-based products in the market, offering incentives for mudarabah-based products, expanding the guarantee facilities to mudarabah contracts, and introducing mudarabah mutanaqisah.